Long non-coding RNA MALAT1 and microRNA-499a expression profiles in diabetic ESRD patients undergoing dialysis: a preliminary cross-sectional analysis - Fawzy, Manal S.; Abu AlSel, Baraah T.; Al Ageeli, Essam; Al-Qahtani, Saeed Awad; Abdel-Daim, Mohamed M.; Toraih, Eman A. (Archives of physiology and biochemistry, 2020)
Background: Circulating non-coding RNAs (ncRNAs) have been implicated in health and disease. This study aimed to evaluate the serum expression profile of microRNA-499a (miR-499a) and its selected bioinformatically predicted partner long-ncRNA MALAT1 (metastasis-associated lung adenocarcinoma transcript 1) in diabetes-related end-stage renal disease (ESRD) patients and to correlate the expressions with the patients' clinicolaboratory data. Subjects and methods: Real-time quantitative polymerase chain reaction was applied in diabetics with and without ESRD (n = 90 for each). Results: Serum MALAT1 expression levels were increased in the ESRD group relative to diabetics without ESRD with median (quartile) values of 10.5 (1.41-126.7) (p < .001). However, miR-499a levels were decreased in more than half of ESRD patients with a median of 0.96 (0.13-3.14). Both MALAT1 and miR-499a expression levels were inversely correlated in the ESRD patient-group. Conclusions: MALAT1 up-regulation and miR-499 down-regulation might be involved in diabetic nephropathy-related ESRD pathogenesis. Functional validation studies are warranted to confirm the MALAT1/miR-499a partnership.